Dried blood spot technique for the monitoring of ambrisentan, bosentan, sildenafil, and tadalafil in patients with pulmonary arterial hypertension - Enderle, Yeliz; Meid, Andreas; Friedrich, Jörg; Grünig, Ekkehard; Wilkens, Heinrike; Haefeli, Walter E.; Burhenne, Jürgen (Analytical chemistry, 2015)
Endothelin receptor antagonists (ERA) and phosphodiesterase 5 inhibitors (PDE5I) are long-term therapeutics for the treatment of pulmonary arterial hypertension (PAH). Their interindividual pharmacokinetic variability is remarkably large, and despite the seriousness of the disease, nonadherence is occurring. Therefore, methods to monitor sufficient circulating drug levels are essential. The objectives of this study were to develop and validate dried blood spot (DBS) assays for the quantification of ambrisentan, bosentan, sildenafil, tadalafil, and their main metabolites. We also quantified the influence of different hematocrit levels and assessed the correlation of simultaneously taken capillary whole blood (DBS) and venous plasma samples. The aliquot punches were extracted by liquid/liquid extraction followed by liquid chromatography/tandem mass spectrometry (LC/MS/MS) quantification methods. All assays fulfilled the requirements of the FDA and EMA guidelines for assay validation with a lower limit of quantification of 2.5 ng/mL for the ERAs, 5 ng/mL for sildenafil, and 10 ng/mL for tadalafil. All analytes were stable for at least 147 days when stored on DBS filter paper cards at room temperature in the dark. Due to poor distribution into erythrocytes, drug concentrations in DBS were always lower than in plasma, resulting in conversion factors of 1.58 for ambrisentan and sildenafil and 1.52 for bosentan and tadalafil.
Gesehen am 13.07.2020